The kinetochore corona orchestrates chromosome congression through transient microtubule interactions - Christopher E. Miles; Fioranna Renda; Irina Tikhonenko; Angus Alfieri; Alex Mogilner; Alexey Khodjakov (Proceedings of the National Academy of Sciences, 2026)
For proper segregation of chromosomes and successful cytokinesis, chromosomes must first “congress”—gather in a tight plate near the spindle equator. Molecular mechanism(s) of congression are not fully understood. Here we combine live-cell microscopy, perturbations of microtubule motor activities, correlative light/electron microscopy, and computational modeling, to quantitatively characterize the early-prometaphase movements that bring the scattered chromosomes to the equator in human RPE1 cells. We find that the early-prometaphase movements are directed toward the center of the spindle axis and not the spindle poles. Centromere velocity of the centripetal movements is not constant, with centromeres moving faster at larger distances from the spindle center. We also detect that numerous short microtubules appear at kinetochores at the earliest stages of spindle assembly and prior to chromosome congression. Computational modeling reveals that a mechanism based on brief, stochastic, minus-end directed interactions between the short microtubules protruding from the kinetochores and long appropriately curved microtubules within the spindle accurately predicts the observed distance-velocity function. Further, the model predicts that insufficient numbers of microtubules protruding from the kinetochores decreases the velocity and randomizes directionality of congression movements. These predictions match changes in the chromosome behavior observed in cells with suppressed nucleation of microtubules at the kinetochore corona (RPE1 Rod Δ/Δ ). In contrast, predictions of computational models based on continuous pulling forces at kinetochores differ significantly from the experimental observations. Together, live-cell observations and modeling reveal a mechanism that enables the efficient and synchronized arrival of chromosomes to the spindle equator.